Evaluation of The Adiwiyata School Program in Enhancing Environmental Care Character at SDN Made I No. 475 Surabaya - Atika Mujahidah; Sholeh Muhammad (Universitas Negeri Surabaya, 2025)
This study aims to describe the Context, Input, Process, Product, and Outcome of the Adiwiyata School Program in developing students’ environmental care character at SDN Made I No. 475 Surabaya. This research employed a qualitative evaluation approach using the CIPPO model (Context, Input, Process, Product, Outcome). Data were collected through observation, interviews, and documentation involving the principal, Adiwiyata coordinator, teachers, parents, and students. The data were analyzed using the Miles and Huberman model, consisting of data collection, condensation, display, and conclusion drawing. The results show that the program is implemented based on government policy and the school’s initiative to create a clean and comfortable learning environment. Adequate human resources, funding, and facilities support the program. The process integrates environmental education and active participation from the school community and parents. The program has successfully shaped students’ environmentally caring behavior, such as cleanliness, waste sorting, and plant maintenance, and has built a clean, disciplined, and eco-friendly school culture extending to their homes and communities.This study was limited to one elementary school, so the findings may not represent all Adiwiyata schools. Future studies could conduct comparative or quantitative research to strengthen generalization. The results highlight the importance of collaboration between schools, parents, and communities in sustaining environmental awareness. This study provides a comprehensive evaluation of the Adiwiyata Program through the CIPPO model, showing its role in fostering students’ environmental character in a sustainable way.